Electrochemically tuned cobalt hydroxide carbonate with abundant grain boundaries for highly efficient electro-oxidation of hydrazine. (8th January 2018) - Yan, Xiaodong; Liu, Yuan; Lan, Jinle; Yu, Yunhua; Murowchick, James; Yang, Xiaoping; Peng, Zhonghua
Abstract : Electrochemical tuning generated grain boundaries in Co(OH) x (CO3 )0.5(2− x ) offer numerous unparalleled active sites for highly efficient electro-oxidation of hydrazine. Abstract : Grain boundaries bear many active sites for surface reactions ( e.g. electrocatalysis and energy storage), and increasing the grain boundaries has become an important strategy to tune the number of surface active sites and the reaction kinetics. Herein, we show that a simple in situ electrochemical tuning method can be used to turn Co(OH) x (CO3 )0.5(2− x ) crystals into interconnected ultrafine nanoparticles with enriched grain boundaries. The grain boundaries offer numerous unparalleled active sites for highly efficient electro-oxidation of hydrazine. The electrochemically-tuned Co(OH) x (CO3 )0.5(2− x ) shows an onset potential (−1.12 V vs. Ag/AgCl) 180 mV smaller than that of the pristine Co(OH) x (CO3 )0.5(2− x ), and delivers a high current density of 62.4 mA cm −2 at −0.90 V vs. Ag/AgCl, which is 27 times higher than that of the pristine Co(OH) x (CO3 )0.5(2− x ) . This work produces the most active non-metallic catalyst for hydrazine oxidation with catalytic activity comparable to the state-of-the-art catalysts. Moreover, our electrochemical tuning method is applicable to other materials ( e.g. Co3 O4, Co(OH)2 and Ni(OH)2 ).